Cricotracheal resection: a rare procedure in adults - Luna Ortiz, Kuauhyama; Ochoa, Cesar O. Cabrera; Ramon, Luis C. Zacarias; Peteul, Zelik Luna; Ortega, Dorian Y. García (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Benign or malignant tumors originating in the cricotracheal region (cricoid cartilage and first tracheal ring) are considered rare events in adult patients. Although there are several treatment options for benign tumors, cricotracheal resection remains the gold standard treatment for malignant tumors. The objective of the present study is to describe the cases that have been treated at our institutions. We selected five cases from a database of 800 clinical records. Three cases were treated at the national cancer institute, Mexico, and two in other institutions. All cases were treated by the same surgeon. Out of four women and one man, with a median age of 52 years, there were two cases of adenoid cystic carcinoma, two of idiopathic stenosis, and one of hemangiopericytoma. All underwent cricotracheal resection with laryngotracheal anastomosis and are still alive. Stenosis or primary tumors of the cricotracheal region can be initially treated with endoscopy. However, cricotracheal resection remains the gold standard treatment as it is a safe surgical procedure with minimal and acceptable sequelae. It also improves disease-free period, overall survival, and quality of life, albeit with a low and acceptable morbidity rate.